The ethics of the new economy : restructuring and beyond (UPCC book collections on Project MUSE., 1998)
"In The Ethics of the New Economy: Restructuring and Beyond, professionals from the fields of philosophy, ethics and management, as well as those representing the groups affected by restructuring, tackle thorny ethical issues."--Jacket